Splenic flexure colonic lipoma causing intussusception - Moussally, Moustafa (JRSM Open, 2021)
Colonic lipomas are rare benign tumours that are usually asymptomatic. However, giant colonic lipomas tend to be symptomatic and can occasionally result in intussusception and intermittent colonic obstruction. As adult intussusception is an uncommon occurrence, the identification of the underlying aetiology is essential due to its high association with malignancy. Computed Tomography remains the tool of choice for the diagnosis of colonic lipomas. Surgical excision remains the mainstay treatment of giant symptomatic colonic lipomas. We hereby present the case of a 51-year-old male found to have a colonic lipoma causing recurrent intussusception. We discuss the approach, diagnostic tools and available treatment modalities for colonic lipomas. We also provide a brief literature review of intussusception in adults.